Gibberellin, shading and pruning height in the production of epicormic shoots in Araucaria angustifolia (Bertol.) Kuntze - de Almeida Maggioni, Renata (2020)
Araucaria angustifolia is a native Brazilian conifer of great economic importance. The difficulty of breaking apical dominance and induction/growth of multiple shoots is characteristic of the species, leading to difficulties in the production of mini-cuttings and formation of a lower open canopy for pinion production in orchards. Thus, this study aimed to evaluate the efficiency of gibberellin application, shading and different pruning heights in overcoming the apical dominance in araucaria seedlings. Seedlings with approximately 4 years old were submitted to three experiments, which were the application of gibberellin (0 mg L-1 GA3 and 500 mg L-1 GA3); shading (full sun and shade house) and different pruning heights (30 cm and 60 cm) from the seedling neck. The application of GA3 promoted smaller number of shoots than the control treatment (0 mg L-1 GA3). There was no influence of shading on shoot length. Pruning at 30 cm promoted the largest number of shoots. Thus, it can be concluded that the cutoff at 30 cm is indicated for the production of multiple shoots in A. angustifolia, neither GA3 application nor seedling shading are necessary for shoot growth.